2005
DOI: 10.1038/435164a
|View full text |Cite
|
Sign up to set email alerts
|

A record-breaking pollen catapult

Abstract: The release of stored elastic energy often drives rapid movements in animal systems, and plant components employing this mechanism should be able to move with similar speed. Here we describe how the flower stamens of the bunchberry dogwood (Cornus canadensis) rely on this principle to catapult pollen into the air as the flower opens explosively. Our high-speed video observations show that the flower opens in less than 0.5 ms--to our knowledge, the fastest movement so far recorded in a plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 7 publications
3
69
0
Order By: Relevance
“…8 Our measurement of 2.65 m/s reflects an amazing consistency given that we were working with different clones in different laboratories. These measurements show Catasetum to be capable of some of the fastest velocities, speeds and accelerations within the plant kingdom and the speed compares favorably to the figure of 3.1 m/s given for the stamens of Cornus canadensis as measured by Edwards et al 3 The mechanism for communicating the stimuli signal within Catasetum is still to be determined but the rapid response of genera such as Dionea has been suggested by Trebacz et al to be due to an action potential involving CA 2+ , Clˉ and K + . 9 A fertile course of inquiry would be to accurately record the moment of contact between a probe and the antennae, the moment of eruption and factor the speed of the signal through the antennae to the area from which the pollinium emerges.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…8 Our measurement of 2.65 m/s reflects an amazing consistency given that we were working with different clones in different laboratories. These measurements show Catasetum to be capable of some of the fastest velocities, speeds and accelerations within the plant kingdom and the speed compares favorably to the figure of 3.1 m/s given for the stamens of Cornus canadensis as measured by Edwards et al 3 The mechanism for communicating the stimuli signal within Catasetum is still to be determined but the rapid response of genera such as Dionea has been suggested by Trebacz et al to be due to an action potential involving CA 2+ , Clˉ and K + . 9 A fertile course of inquiry would be to accurately record the moment of contact between a probe and the antennae, the moment of eruption and factor the speed of the signal through the antennae to the area from which the pollinium emerges.…”
Section: Discussionsupporting
confidence: 77%
“…9 However our figure for acceleration was far less than the 24,000m/s 2 recorded by Edwards et al for the accelerating stamens of Cornus canadensis. 3 Force. In order to calculate the force the pollinium was exerting it was necessary to find its weight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to these active mechanisms, the N. gracilis lid movement requires neither mechanical preloading nor physiological activation. The fastest reported plant movements-up to 170 ms −1 in extreme cases-are catapult-based mechanisms for seed dispersal (5,39,40), spore release (6), and pollen transfer (7,41). These superfast motions invariably rely on irreversible, singleshot mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Ren (2010) suggested that there are four main types of stamen movement: cascade movement (Weigend and Gottschling, 2006); quick and explosive movement (Taylor et al, 2006); simultaneous and slow movement (Azuma et al, 2005); and stimulated movement (Lechowski and Bialczyk, 1992;Lebuhn and Anderson, 1994). Stamen movement can affect the reproductive biology of fl owering plants because this mechanism forces the visitors to enter fl owers and may alter the interaction plant-pollinator (Schlindwein and Wittmann, 1997;Edwards et al, 2005;Liu et al, 2006;Ren, 2010).…”
mentioning
confidence: 99%